Principio de dignidad humana frente a las trabajadoras sexuales migrantes venezolanas municipio de Sabanalarga Atlántico periodo 2019-2022 (2022)
Opting for sex work in order to meet basic needs goes against human dignity, because it is a job with an unfair salary, mistreatment, humiliation or others. Thus, this research had the purpose of studying the situation of sex work in immigrants in the municipality of Sabanalarga Atlántico, and especially, in the face of the principle of human dignity. Through a Socio-legal investigation that is supported by an analysis of mixed data (Qualitative-Quantitative) that already contributes to verify the principle of human dignity against Venezuelan immigrant sex workers in the zone of cordiality in the municipality of Sabanalarga Atlantic period 2021 -2022; Likewise, determine the factors associated with the situation of Venezuelan immigrant sex workers in the municipality, in order to establish the constitutional and legal provisions for the protection of sex workers in order to propose an improvement plan that guarantees decent conditions for women. Venezuelan immigrant women. Through this research, it was observed that the majority of women dedicated to prostitution meet different risk factors that lead them to situations of vulnerability of rights and the principle of human dignity, different limits of their lives that go from the most private to the most public.